Nutritional properties of underutilized legumes and intercropped maize - Ayilara, Modupe S.; Abberton, Michael; Oyatomi, Olaniyi A.; Odeyemi, Olu; Babalola, Olubukola O. (Frontiers in Soil Science, 2023)
Over the years, intercropping which is majorly carried out on legumes and cereal has been practiced to maximize the utilization of land resources and increase the productivity over a piece of land. Most studies on intercropping focus on the yield and yield parameters, leaving out other important aspects such as the nutritional value of the harvested crops. Underutilized legumes are crops which have very scanty information available on them which reduces their general acceptability and utilization. The effects of intercropping on the nutrient status of underutilized legumes and maize in an intercropping system are not well understood. Therefore, the objective of the research was to assess the effect of intercropping on the nutrient and antinutrient parameters of African Yam Bean (AYB), and Winged bean (WB) when monocropped and when intercropped with maize. Hence, this research sought to answer the following questions: (i) does intercropping with maize affect the nutrient and anti-nutrient properties of AYB and WB (ii) does intercropping with AYB and WB and the application of urea fertilizer affect the nutrient and anti-nutrient properties of maize. Five accessions each of AYB and WB were separately intercropped with two accessions of maize. The research was carried out on the research field of the International Institute of Tropical Agriculture, Ibadan, Nigeria. The field was laid out in a Randomized Complete Block Design in triplicates. The treatment consisted of sole and intercropped legumes and maize as well as maize planted with urea fertilizer. The result from the research revealed that intercropping had effects on the nutrient and anti-nutrient properties of AYB, WB and maize, even though each accession responded differently to the intercropping. For instance, in the legumes, intercropping with M2 led to a reduction in the moisture content of AYB accessions TSs4, TSs30, and TSs77, and an increase in the moisture content in winged bean accession Tpt51. Equally, a reduction in the protein content of African yam bean accessions TSs4 and 101 when intercropped with both maize accessions was observed (P ≤ 0.05). On the other hand, an increase was observed in the protein content of AYB accession TSs30 (intercropped with M2), as well as WB accession 15-4 (intercropped with M2) and Tpt51 (intercropped with M1). A reduced tannin content was observed in WB accession Tpt12 intercropped with both maize accessions, while an increased the tannin content was observed in AYB accessions TSs4, TSs101, and WB accessions 15-4, and Tpt32 when intercropped with both maize accessions (P ≤ 0.05). Finally, intercropping increased the fat content in both maize accessions, increased the tryptophan content of M1 when intercropped with Tpt32, and increased the carbohydrate content in M1 intercropped with Tpt51. In conclusion, the results from this experiment revealed that intercropping affected the nutritional and antinutritional properties of the maize and legumes. Of all the Accessions of the underutilized legumes used, AYB accession TSs30 responded better to intercropping by having a better nutritional value (an increased ash, protein, fat and carbohydrate contents as well as a reduced moisture content); it is therefore necessary to further explore this accession to ensure that the potentials embedded in itis maximally tapped into to enhance food security.